Optimal Designs Of The Double Sampling X Chart Based On Parameter Estimation - Teoh, Wei Lin (2013)
Control charts, viewed as the most powerful and simplest tool in Statistical Process Control (SPC), are widely used in manufacturing and service industries. The double sampling (DS) X chart detects small to moderate process mean shifts effectively, while reduces the sample size. The conventional application of the DS X chart is usually investigated assuming that the process parameters are known. Nevertheless, the process parameters are usually unknown in practical applications; thus, they are estimated from an in-control Phase-I dataset. In this thesis, the effects of parameter estimation on the DS X chart’s performance are examined. By taking into consideration of the parameter estimation, the run length properties of the DS X chart are derived. Since the shape and the skewness of the run length distribution change with the magnitude of the process mean shift, the number of Phase-I samples and sample size, the widely applicable performance measure, i.e. the average run length (ARL) should not be used as a sole measure of a chart’s performance. For this reason, the ARL, the standard deviation of the run length (SDRL), the median run length (MRL), the percentiles of the run length distributions and the average sample size (ASS) are recommended to effectively evaluate the proposed DS X chart with estimated parameters.